Hub Genes Involved in the Progression of Nonalcoholic Fatty Liver Disease to Hepatocellular Carcinoma - Liu, Baiyi; Wang, Xiaoxiao; Wu, Nan; Liu, Feng; Rao, Huiying (Current Medicinal Chemistry, 2025)
BackgroundNonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide. With an increasing number of patients, NAFLD has been identified as a risk factor for Hepatocellular Carcinoma (HCC). The precise pathophysiology of NAFLD-related HCC has not been completely understood recently.ObjectiveWe analyzed the hub genes related to NAFLD and HCC to predict the risk of NAFLD progressing to HCC.MethodsTwo datasets of NAFLD were used to identify differentially expressed genes. Lasso-Cox regression analysis was performed to determine a gene model to predict the risk of the progression from NAFLD to HCC. Three validation datasets were analyzed to evaluate the performance of the gene model, including normal and NAFLD with fibrosis, NAFLD with fibrosis and NAFLD-related HCC, and normal and NASH-related HCC.ResultsSeven genes, including COL1A1, TIPM1, VCAN, FOS, CD79A, CXCL9, and VWF, were identified as the hub genes, and then a gene model was constructed. By calculating, the area under the receiver operating characteristic curves (AUCs) for risk prediction were 0.97, 0.886, and 0.751 in the three validation datasets, respectively. Gene set enrichment analysis indicated that the MAPK, TGFβ, p53, PPAR, insulin signaling pathways, and fatty acid metabolism were significantly upregulated in the high-risk group. GTPase activity and intrinsic apoptotic signaling pathway had significant upregulation in the low-risk group.ConclusionThe seven hub genes may predict the risk of NAFLD developing into HCC by mediating the potential molecular mechanism, which could be used as biomarkers for predicting the progression, diagnosis, and treatment of NAFLD.
Keywords: biomarkers